Examining the reliability and validity of students’ self-efficacy beliefs, stress, perceived teachers’ support and academic burnout scales using PLS-SEM approach - Jingyuan Li; Yoon Fah Lay (Conscientia Beam, 2025)
Likert scales were used in this study to collect data on measures such as the student academic burnout scale, the student stress scale, the student self-efficacy beliefs scale and the student perceived teacher support scale. The purpose of this study is to examine the four-part scales' reliability and validity used in this research. The number of measurement indicators for the four scales was 11, 13, 12 and 10, respectively. Seventy-five college students from five colleges and universities participated in the research and the partial least squares structural equation modelling (PLS-SEM) approach was applied to analyze the data. Consequently, the internal consistency and reliability of the measures were assessed using Cronbach's alpha (CA) and composite reliability (CR) both of which exceeded the clinical thresholds of 0.6 and 0.7, respectively. The average variance extracted (AVE) was used to evaluate the scales' convergent validity and the reported values were all stated above 0.5. The scales' discriminant validity was also framed within the range of threshold values. As a result, the scales used in this study demonstrated good validity and reliability and can be useful in assessing relationships throughout a range of study situations.